2021
DOI: 10.3390/foods10051134
|View full text |Cite
|
Sign up to set email alerts
|

The Egg Yolk Content in ω-3 and Conjugated Fatty Acids Can Be Sustainably Increased upon Long-Term Feeding of Laying Hens with a Diet Containing Flaxseeds and Pomegranate Seed Oil

Abstract: Long-term feeding trials examining the incorporation of conjugated linolenic acids (CLnA) into the diet of laying hens are lacking. In the present study, we compared two diets in sixty-six red Sex-Link hens (33 hens/treatment), fed for 26 weeks. The control diet was high in oleic acid, while the test diet was high in α-linolenic acid (ALA) and punicic acid (PunA). No significant differences were observed between treatments for hens’ performance, egg weight and yolk weight. In contrast, dietary ALA and PunA res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…On the contrary, Ngo Njembe et al. (2021) could not find any effect of dietary supplemental 7 wt% PSO mixed with 7.5% flaxseed oil on the laying performance of laying hens. Thus, further investigations are needed to evaluate the effect of PSO on laying performance.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…On the contrary, Ngo Njembe et al. (2021) could not find any effect of dietary supplemental 7 wt% PSO mixed with 7.5% flaxseed oil on the laying performance of laying hens. Thus, further investigations are needed to evaluate the effect of PSO on laying performance.…”
Section: Discussionmentioning
confidence: 88%
“…(2017) and Ngo Njembe et al. (2021) when birds fed on diets supplemented with PSO or a combination of PSO and flaxseed oil, respectively. In this regard, the deposition of DHA or EPA increased in the egg yolk of birds fed PSO supplemented diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that CLnA could be taken up by the body upon long term feeding with a diet containing PSO. 10 PA is considered a potential regulator of lipid metabolism, and several studies have confirmed the advantageous effects of PA against obesity and related liver injury. [11][12][13] In addition, PA has been acknowledged as a heme oxygenase-1 inducer that can alleviate nonalcoholic fatty liver disease (NAFLD).…”
Section: Introductionmentioning
confidence: 99%
“…However, Fats are well-known energy sources that have a direct impact on the laying hen's body, ensuring that their growth, sustainability, and production requirements are met, since the quality and cost of the eggs are linked, it's critical to choose an appropriate fat source for use in chicken feed, as this will have an impact on both production and the overall health of the chickens (9 and 13). Recently, the cost of using vegetable oils has become a factor that burdens specialists in the poultry industry, whether at the level of meat or egg production, which has led to an increase in feed prices in general, which prompted them to think of an alternative source for vegetable oils, such as ruminant fat (Ruminants Tallow) (19). Ruminant fat is one of the most important sources of animal fats and a means by which a very rich source of nutritional energy can be recycled, fat-soluble vitamins and other key nutrients, It is worth noting that although animal fats have benefits, the most important of which is the high energy they contain and their high economic returns as they are considered lowcost, the negative reputation that accompanied these fats for many years is difficult to change represented by the risk of cardiovascular disease, Although, it has been proven that animal fats extracted from ruminant fats contain unsaturated fatty acids known as isomers(isomers of unsaturated fatty acids) the product of natural hydrogenation by microorganisms inside the rumen of ruminants, The most important of which are Transvaccenic acid (TVA), rumen (RMA) Rumenic acid and Trans-palmitoleic acid (TPA) these acids are considered neutral towards cardiovascular health, but their use is still debated between supporters and opponents (11).…”
Section: Introductionmentioning
confidence: 99%